Nails binding ikat textile design / Firdaus Mhd Jakin, Effa Izzwanna Mohamad Nor and Norwani Md Nawawi - Mhd Jakin, Firdaus; Mohamad Nor, Effa Izzwanna; Md Nawawi, Norwani (Research Innovation Business Unit, 2014)
Tie-dye is believed to have been practiced early in history by people in many parts of the world and in Malaysia it is called “kain plangi”. “Kain Plangi”is the first batik which existed in the 17th century in Malaysia. Binding Ikat is a resist-dyeing method of patterning fabric created by withholding dye on certain area of the fabric. It consists of binding certain parts of the cloth in such way that when it is dyed, the dye is unable to penetrate into these areas and the method and effect of resist dyeing are various. The design effect based on the experiment conducted where the outcome of design patterns produced is influenced by the type of nails. The fabric used also play a big influence over the final result of the design pattern. The result of experiments conducted clearly shows that design patterns differ depending on nail size play a crucial role in these experiments. The design effect produced using tie-dye technique is unlimited and unpredictable. The material used for binding also influences the process of producing the binding ikat design because it can prevent colours from penetrating into other area. Then the selection of different types of fabric is another influence on the design. These areas are visible results seen on fabric cotton, chiffon and calico. Design pattern on cotton and chiffon are full and compact while the colours are bright and different with calico fabric where the design pattern produced on this cloth are sparse while the colours are dull to poor absorption. The colours are one of the main components in the creation of design pattern tie-dye technique. The colours give varieties to the design patterns produced through the experimental process intermixing colours, different design pattern were then created. In addition, the fishing lines used for tying process and applying different types of technique also can give differences of the ikat design. The design was formed and may look like spider web or diamond pattern. The fishing line is the core material used for tying the fabric in the experiment and named binding ikat or tie-dye technique. This can be seen on the design pattern created on the fabric in the shape circle and white lines. The design is created when any string was tied for tying onto the fabric which prevented the colours from absorption. Hence the bind surface will remain as white to reveal the original base colour. At the end of the experiment, it was observed that there are interesting design pattern produced using various types binding technique including size and type nails used. The result can to generate idea by introducing a new product and artwork. This provides exposure to Malaysians on the aesthetic and the beauty of “kain plangi” as an aspiring design to create artwork. The design can be anything about the pattern of Islam especially the fashion, soft furnishing, artwork and etc. The design produced different and unplanned design patterns